Effects of dietary protein and inulin on growth and nitrogen balance in growing pigs. - Loh, Teck Chwen; Foo, Hooi Ling; Wang, Wei Shan (Taylor & Francis, 2010)
This study was conducted to determine the effects of dietary protein and inulin on growth, nitrogen balance and feces characteristics in growing pigs. The diet treatments were two levels of CP, 18% and 14% with or without 0.3% inulin addition. Daily live weight gain (DLWG) and feed conversion ratio (FCR) were not affected by the dietary treatments. However, N intake and N excretion were decreased (P<0.05) with reduced CP level. Addition of inulin had no effect on the total amount of N excretion, but tended to shift N excretion from urine to feces. It is concluded that reduction of dietary CP up to 14% in diet of growing pigs will reduce N excretion and thereby environmental pollution.